Bioaccumulation of metals in aquatic insects of streams located in areas with sugar cane cultivation - Corbi, Juliano José; Froehlich, Claudio Gilberto; Strixino, Susana Trivinho; Santos, Ademir dos [UNESP] (Sociedade Brasileira de Química, 2010)
Streams located in areas of sugar cane cultivation receive elevated concentrations of metal ions from soils of adjacent areas. The accumulation of metals in the sediments results in environmental problems and leads to bioaccumulation of metal ions by the aquatic organisms. In the present study, bioaccumulation of the metals ions Al, Cd, Cr, Cu, Fe, Mg, Mn and Zn in aquatic insects in streams impacted by the sugar cane was evaluated. The results pointed out that the insects were contaminated by the sediment and that the collector organisms as Chironomus species accumulated higher concentration of metals than the predator organisms.
Keywords: metals; bioaccumulation; trophic transfer